The Development of River School as a Community Empowerment Facility at Tegaltirto, Berbah, Sleman Regency - Ambar Teguh Sulistiyani; Budi Kamulyan; Muammar Yuliana; Kristi Yuliani; Susilowati Myrra Dewi (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2021)
river as one of the providers and buffers of life must always be preserved. The sustainability of the river ecosystem is necessary so that water availability can be maintained over time both in quantity and quality. Attention to community behavior is the main target to guarantee the conservation of river water. River pollutants are increasing in quantity due to both domestic and production activities. Community empowerment aspect should always be improved especially in taking care of maintenance and utilization sustainability of the river for human life in particular and ecosystem in general. Tegaltirto Village which is crossed by the Opak River is very important to be preserved especially in proper river management. Community service in the form of institutional development of river school is needed. The scheme is appropriate to educate, assist, and initiate a proper and sustainable community empowerment forum. The research methods in the empowerment of a river school institution are focused on the participatory empowerment aspect. Data collection was done through interviews, documentation, and focus group discussions. The knowledge and skills of the river school institution are transferred through training and an intensive facilitation program. The preparation of the followup plan was done through assistance by UGM Team. This was to realize the organizational structure that was responsible for the management and utilization of river resources. The implementation of a river school institution in Tegaltirto Village cannot be separated from the community participation and the observer of river conservation in the spirit of building the village. Conservation and sustainability of water and river utilization become the implementation motivation for the river school activity in Tegaltirto village.